Cytomegalovirus prophylaxis using low-dose valganciclovir in patients with acute leukemia undergoing allogeneic hematopoietic stem-cell transplantation. (March 2021) - Li, Po-Hsien; Lin, Cheng-Hsien; Lin, Yu-Hui; Chen, Tsung-Chih; Hsu, Chiann-Yi; Teng, Chieh-Lin Jerry
Background: Letermovir prophylaxis is currently the standard of care for the prevention of cytomegalovirus (CMV) infections in allogeneic hematopoietic stem-cell transplantation (allo-HSCT). However, drug–drug interactions between letermovir and azoles or calcineurin inhibitors and the high financial burden of letermovir remain problematic, especially in resource-limited countries. It has not been clarified whether a lower dose of valganciclovir would constitute an effective strategy for CMV prevention in patients with acute leukemia undergoing allo-HSCT. Methods: We retrospectively assessed 84 consecutive adult patients with acute leukemia who underwent allo-HSCT. These 84 patients were stratified into a valganciclovir prophylaxis group ( n  = 20) and a non-valganciclovir prophylaxis group ( n  = 64). Results: Patients in the valganciclovir prophylaxis group had a lower possibility of CMV DNAemia at week 14 after allo-HSCT than those in the non-valganciclovir prophylaxis group (15.0% versus 50.0%; p  = 0.012). The cumulative incidence of CMV DNAemia at week 14 was also lower in patients with valganciclovir CMV prophylaxis than in those without (15.0% versus 50.4%; p  = 0.006). Multivariate analysis validated these data, showing that a low dose of valganciclovir significantly reduced the risk of CMV DNAemia at week 14 by 88% (hazard ratio: 0.12; 95% confidence interval: 0.04–0.42; p  = 0.001). However, these two groups had similar overall survival rates at week 48 (75.0% versus 76.6%; p  = 0.805). Four of 20 (20%) patients discontinued valganciclovir prophylaxis because of adverse events. Conclusion: Low-dose valganciclovir prophylaxis could be an alternative to letermovir to prevent CMV infection in allo-HSCT, especially in resource-limited countries.